Mapeamento geomorfométrico do município de Analândia (SP) - Silva, Rodrigo Rodrigues Graneiro [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This research aimed to study the relief characteristics of the city of Analândia (SP) considering geomorphometric variables, based on the elaboration of geomorphometric maps of the region. Geomorphometry is the science that uses parameters of enormous relevance for the analysis of terrain in a digital environment. thus, we sought especially as slope orientations, slope and curves, both horizontal and vertical, using two several altimetric bases. In order to show the differences of the altimetric bases made in the comparative analysis of mappings, digital terrain elevation models (MDETs) were used, through which, with the geographic information system (GIS), digital modeling was obtained, highlighting the characteristics of the relief in three dimensions, this environment is necessary for an analysis in geomorphometry. The altimetric data came from the base of topographic charts in scale 1: 50,000 of the Brazilian Institute of Geography and Statistics (IBGE) and as second base, the altimetric data from the SRTM (Shuttle Radar Topography Mission) base modified by the National Institute of Space Research (INPE) in the Topodata project. The construction of the geomorphometric maps of the municipality of Analândia (SP) led to a quantitative survey of the relief, through which results were obtained that clarified the advantages and limitations of using the research procedure in the presented scale. The analyzes made it possible to clarify which basis presents better results in the presentation of strands and which base best represents the top sectors

Esta pesquisa visou estudar características do relevo do município de Analândia (SP) considerando variáveis geomorfométricas, a partir da elaboração de mapas geomorfométricos da região. A Geomorfometria constitui-se como a ciência que se utiliza de parâmetros de enorme relevância para análises dos terrenos em meio digital. Assim, buscou-se avaliar especialmente as orientações de vertentes, declividade e curvaturas, tanto horizontais quanto verticais, utilizando duas e distintas bases altimétricas. Para expor as diferenças das bases altimétricas feitas na análise comparativa de mapeamentos, utilizaram-se modelos digitais de elevação do terreno (MDETs), por meio dos quais, junto ao sistema de informação geográfica (SIG), se obteve a modelagem digital, realçando as características do relevo em três dimensões, ambiente este necessário para uma análise em geomorfometria. Os dados altimétricos foram provenientes da base de cartas topográficas em escala 1:50.000 do Instituto Brasileiro de Geografia e Estatística (IBGE) e como segunda base, os dados altimétricos provenientes da base SRTM (Shuttle Radar Topography Mission) modificada pelo Instituto Nacional de Pesquisas Espaciais (INPE) no projeto Topodata. A construção dos mapas geomorfométricos do município de Analândia (SP) levou a uma investigação quantitativa do relevo, por meio da qual obtêm-se resultados que esclareceram as vantagens e limitações de uso do procedimento de pesquisa na escala apresentada. As análises realizadas permitiram esclarecer qual base apresenta melhores resultados na apresentação de vertentes e qual base melhor representa os setores de topo
Keywords: Geomorfologia; Relevo (Geografia); Mapas topograficos; Sistemas de informação geográfica; Sensoriamento remoto; Analândia (SP)